COVID-19 and Spillover Effect of Global Economic Crisis on the United States’ Financial Stability - Shehzad, Khurram; Xiaoxing, Liu; Bilgili, Faik; Koçak, Emrah (Frontiers in Psychology, 2021)
Due to the Novel Coronavirus pandemic (COVID-19), Lockdown engendered has a vicious impact on the global economy. This analysis's prime intention is to evaluate the impact of the US's economic and health crisis as a result of COVID-19 on its financial stability. Additionally, the investigation analyzed the spillover impact of the worldwide economic slowdown experienced by COVID-19 on the US's financial volatility. The study applied an Autoregressive Distributed Lag (ARDL) model and discovered that the economic and health crises that occurred in the US portentously upset the future expectations of its investors. Conspicuously, the health crisis in Spain and Italy ominously spillovers the US's financial instability in the short run. Likewise, the economic crisis ensued in the UK because of COVID-19, spillover the US markets' financial instability. The examination evaluated that Asian and African nations' economic crisis perilously affects the US's financial stability. The study determined that financial instability occurred in the US due to its own economic and health crises persist for a longer period than financial disequilibrium that occurred in the other nations. The analysis suggested some strategies of smart lockdown that the Government of the US and other nations should follow to begin the economic cycle through tighter controls to minimize losses by following the steps of, e.g., (a) Preparing a lockdown checklist, and (b) Monitoring completion of lockdown tasks and (c) Complete a close-down stock take or count.